2021
DOI: 10.24251/hicss.2021.109
|View full text |Cite
|
Sign up to set email alerts
|

An Approach for Weed Detection Using CNNs And Transfer Learning

Abstract: To prevent yield losses, it is critical to eliminate competition between food crops and weeds at the onset of plant growth. While uniform spraying of herbicides can be economically and environmentally inefficient, site-specific weed management (SSWM) counteracts this by reducing the amount of chemical application with localized spraying of weed species. Past research on weed detection in SSWM has used a large deep convolutional neural network (DCNN) for weed detection. These models are, however, computationall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…In the first stage of the proposed approach, stateof-the-art models with pre-trained weights were trained on the plant seedling dataset. The result of this baseline (average 91.5% prediction accuracy) was comparable to the earlier result of prior studies that employed the same dataset [42], [51]- [53]. Further, the literature points to a relationship between model accuracy and model compression such that pruning models could result in decreased accuracy [38], [39].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In the first stage of the proposed approach, stateof-the-art models with pre-trained weights were trained on the plant seedling dataset. The result of this baseline (average 91.5% prediction accuracy) was comparable to the earlier result of prior studies that employed the same dataset [42], [51]- [53]. Further, the literature points to a relationship between model accuracy and model compression such that pruning models could result in decreased accuracy [38], [39].…”
Section: Discussionsupporting
confidence: 77%
“…Each techniquetransfer learning; model compression; and ensemble learningdelivers benefits that can enhance and underpin the generalizability of DL to precision agriculture systems. Transfer learning, where a model trained on one task can be ported to another task, offers opportunities for reducing overfitting and ensuring robust results in the face of limited training data [51]. Model compression offers additional benefits for reducing the size of the DL models, which means an equivalent reduction in both energy consumption and inference time [33].…”
Section: Discussionmentioning
confidence: 99%
“…To make the algorithms more manageable for hardware with low resources while still retaining accuracy, in this study [ 127 ] the authors used ensemble learning approaches, transfer learning, and model compression. The suggested method was carried out in three steps: transfer learning, pruning-based compression, quantization, and Huffman encoding, and model ensembling with a weighted average for improved accuracy.…”
Section: Summary Of Identified Articles In Slrmentioning
confidence: 99%
“…Regarding greener DL models in applications domains, we can find advances for greener DL-based solutions as well. For instance, for weed detection, Ofori et al combined the mobile-sized EfficientNet with transfer learning to achieve up to 95.44% classification accuracy on plant seedlings [20], and model compression achieving 62.22% smaller in size than DenseNet (the smallest-sized full-sized model) [21]. Moreover, for pig posture classification, Witte et al reported the YOLOv5 model achieving an accuracy of 99,4% for pig detection, and EfficientNet achieving a precision of 93% for pig posture classification [22].…”
Section: Green Aimentioning
confidence: 99%